AGAMA DAN KONTRIBUSINYA DALAM MEMECAHKAN PROBLEMA SOSIAL DALAM MASYARAKAT PLURAL - H. Muhazzab Said (AL TAJDID, 2009)
Al-Qur,an explain that the only Islam is the received religion. Islam generates all dimension in relation to human life. It taught how to conduct relation to the God, among them, and to the other creation. In other side, every religion has certain characteristic compare others. So, each religion teach moral to contribute in solving the social problem in society, specially in plural society.  To solve the social problem, need a normative base, moral and ethic. Religious aspect plays an important role to carry out the verse of God, namely transendental and spiritual dimension an also social dimension which is contain ethic and moral. So this paper will explain how does religion contribute in solving the social problem in plural society.